Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1115/1.4030162
|View full text |Cite
|
Sign up to set email alerts
|

Products' Shared Visual Features Do Not Cancel in Consumer Decisions

Abstract: Consumers' product purchase decisions typically involve comparing competing products' visual features and functional attributes. Companies strive for “product differentiation” (Liu et al., 2013, “Product Family Design Through Ontology-Based Faceted Component Analysis, Selection, and Optimization,” ASME J. Mech. Des., 135(8), p. 081007; Thevenot and Simpson, 2009, “A Product Dissection-Based Methodology to Benchmark Product Family Design Alternatives,” ASME J. Mech. Des., 131(4), p. 041002; Kota et al., 2000, “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Previous research has found correlations between the provision of sustainability-related information and engendered emotions, e.g., [21,25]. The diverging outcomes arisen from the present study, where this information is less explicit, seem to confirm the differences caused by diverse information fashions as discussed by Du and MacDonald [66]. To investigate the ease of individuating features ascribable to eco-design, the authors plan to exploit the experiment's outputs further and analyze participants' observation of specific Areas of Interest in the pictures, which is enabled by ET results.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Previous research has found correlations between the provision of sustainability-related information and engendered emotions, e.g., [21,25]. The diverging outcomes arisen from the present study, where this information is less explicit, seem to confirm the differences caused by diverse information fashions as discussed by Du and MacDonald [66]. To investigate the ease of individuating features ascribable to eco-design, the authors plan to exploit the experiment's outputs further and analyze participants' observation of specific Areas of Interest in the pictures, which is enabled by ET results.…”
supporting
confidence: 75%
“…This introduces a fundamental bias with respect to a real-word purchasing decision scenario, apart from certain circumstances potentially applying to e-commerce. Besides, Du and MacDonald [66] found different cognitive responses between shared text attributes and shared image features based on data collected through a survey and the monitoring of gaze behavior during the comparison of products' pictures. As aforementioned, survey-based studies might have failed to include unconscious aspects by either neglecting the chance to use biometric instruments for monitoring spontaneous reactions or overlooking the attitude-behavior gap.…”
Section: Rationale and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data provided a different dimension of information when used with other forms of data (for example, survey data). References [4], [20], [27], and [28] summarize uses of eye movement data in product design research. This paper uses fixations, or "eye movements that stabilize the retina over a stationary object of interest" [29], to study areas of interest (AOIs), which refer to "areas of a given stimulus related to the research hypothesis" [27].…”
Section: Effects Of Body Shape and Features On Consumermentioning
confidence: 99%
“…In the past, cue building has been used in industrial design as an art, without understanding how cues are formed or which cues are the most effective. Past research indicates that product visuals do not always behave as one might predict; for example, shared visual features between products are not ignored but rather magnified in judgments [4]. Thus, designers should approach the design of new visual cues carefully.…”
Section: Introductionmentioning
confidence: 99%